Community-Based Initiative to Improve Elderly Health and Quality of Life in Aan Village, Banjarangkan Sub-District, Klungkung Regency - A A I N Marhaeni; Ni Nyoman Yuliarmi; Made Kembar Sri Budhi; Made Santana Putra Adiyadnya; Diah Pradnyadewi; Dewa Jati Primajana; Gede Andika (Journal of Community Service and Empowerment, 2025)
Improving the quality of life for the elderly is essential for fostering a healthier, more prosperous society in Indonesia. In Aan Village, Banjarangkan Sub-district, Klungkung Regency, this goal is pursued through health check-ups, educational sessions by experts, and tailored exercises for the elderly. The program aims to enhance the physical and mental well-being of elderly residents via targeted educational and health initiatives. The program's objectives include: 1) Providing Information, Education, and Communication (IEC) on physical and mental health to improve Knowledge, Attitudes, and Practices (KAP); 2) Educating the elderly on age-appropriate physical exercises to boost health; and 3) Conducting health check-ups to guide subsequent health interventions. These check-ups, performed by trained medical students, assess blood pressure, cholesterol, and blood sugar levels. Following these evaluations, doctors offer tailored advice and physical activities designed to promote health. Results indicate significant improvements in awareness and participation among the elderly, with increased engagement in physical activities and proactive health measures. Common health issues identified include high blood pressure, sugar, and cholesterol levels, with referrals made for further treatment. Challenges include unstable health conditions, difficult access, and scheduling conflicts with traditional events. Recommendations for future programs include enhancing accessibility, offering flexible schedules, and improving facilities. Despite obstacles, the initiative positively impacts elderly well-being and serves as a model for replication in other villages, contributing to the sustained welfare of Indonesia’s aging population.